The cytotoxic necrotizing factors from Yersinia pseudotuberculosis and from Escherichia coli bind to different cellular receptors but take the same route to the cytosol - Blumenthal, Britta; Hoffmann, Claudia; Aktories, Klaus; Backert, Steffen; Schmidt, Gudula (Infection and Immunity, 2007)
The cytotoxic necrotizing factors CNF1 and CNF2 produced by pathogenic Escherichia coli strains and CNFY of Yersinia pseudotuberculosis constitutively activate small GTPases of the Rho family. They deamidate a glutamine (Gln63 in RhoA), which is crucial for GTP hydrolysis. CNF1 and CNFY exhibit 61% identity on the amino acid level, with equal distribution over the whole molecule. Although the two toxins are homologous in the receptor binding domain, we show that they bind to different cellular receptors. CNFY does not enter Caco-2 and CHO-K1 cells, which are responsive to CNF1. In contrast, HeLa, Hep-2, and HEK 293 cells do respond to both toxins. Competition studies with catalytically inactive mutants of the toxins revealed that binding of CNF1 has no influence on the uptake of CNF Y into HeLa cells. In contrast, uptake of CNF1 is retarded after preincubation of HeLa cells with the catalytically inactive mutant of CNF Y, suggesting that the toxin receptors overlap. Moreover, we compared the pathways of the toxins from receptor binding into the cytosol and showed that both toxins are taken up independent of the presence of clathrin or lipid rafts and are released into the cytosol from acidified endosomes. Copyright © 2007, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up